Disclosure Tone and Shareholder Litigation - Rogers, Jonathan L.; Van Buskirk, Andrew; Zechman, Sarah L. C. (The Accounting Review, 2011)
ABSTRACT We examine the relation between disclosure tone and shareholder litigation to determine whether managers' use of optimistic language increases litigation risk. Using both general-purpose and context-specific text dictionaries to quantify tone, we find that plaintiffs target more optimistic statements in their lawsuits and that sued firms' earnings announcements are unusually optimistic relative to other firms experiencing similar economic circumstances. These findings are consistent with optimistic language increasing litigation risk. In addition, we find incrementally greater litigation risk when managers are both unusually optimistic and engage in abnormal selling. This finding suggests that firms can mitigate litigation risk by ensuring that optimistic statements are not contradicted by insider selling. Finally, we find that insider selling is associated with litigation risk only when contemporaneous disclosures are unusually optimistic. JEL Classifications: G38; K22; M41; M48. Data Availability: Data are available from sources indicated in the text.